The Relevance of Behavioral Engineering Model for Productivity Optimization in a Fast-Growing Private Learning Institutions - Arif, Lily Suriani Mohd; Shaari, Roziana; Samah, Irza Hanie Abu; Saidi, Mas Idayu; Rahim, Nur Syafiqah A.; Wahab, Shah Rollah Abdul (Journal of Ecohumanism, 2024)
Optimising performance in the workplace is increasingly becoming a strategic agenda in companies. This interest is fuelled not only by economic and competitive pressures, but also by a growing awareness of the need to improve the prospects of individuals or employees. This article provides an overview of the contributions of the Behavioural Engineering Model (BEM) to optimising the performance of work systems. Proper organisational performance management usually contributes to the long-term benefit of both the organisation and the individual. This model comprises two main elements: the environment and the individual. The employee opinion survey regarding their views on the organisation (satisfaction) was conducted according to the BEM model to illustrate how employee behaviour, performance and performance are related.